Evaluation of the relationship between dyssynchrony and myocardial fibrosis markers in patients with cardiac resynchronization therapy (Annals of Medical Research, 2021)
Aim: Dyssynchrony can be seen in some patients with heart failure. The goal of cardiac resynchronization therapy (CRT) is the correction of dyssynchrony. The correction of myocardial loading and remodel-ing prevents development of the myocardial fibrosis. The aim of this study is to evaluate myocardial fibrosis markers in patients with heart failure CRT applied and to assess the relationship between these markers and dyssynchrony. Material and Methods: Fifty one patients (ejection fraction (EF) ≤ % 35, QRS duration ≥130 msec) were included into the study. Electrocardiography (ECG), 6 minute walking test, and echocardiography were applied before and 6 months after CRT to all patients. Furthermore, Type I Collagen C-Terminal Propeptide (PICP), Type I Collagen C-Terminal Telopeptide (ICTP) levels and PICP/ICTP ratio were studied as myocardi-al fibrosis markers in blood samples.Results: It is observed that QRS was shortened after CRT (p=0.0001). Six minute walking distance was in-creased 6 months after CRT (p=0.0001). PICP level measured before CRT as 560.2 ± 300.4 µg/L while it is measured as 476,9±285,8 µg/L 6 months after CRT (p=0.004). PICP/ICTP ratio before and 6 months after CRT was 9.7 ± 10 and 37.1 ± 32.8 respectively (p=0.0001). It is determined a negative relationship between EF and PICP level and PICP / ICTP ratio (p=0.008, r = -0.37).Conclusion: Our results show that CRT reduces the left ventricular dyssynchrony and consequently leads to favor-able changes in myocardial fibrosis markers. Reducing the mechanical stresses on left ventricle and returning of consequent remodeling may be one of the important mechanisms in the prevention of cardiac fibrosis.